PENGARUH BAHAN BAKAR PERTAMAX DAN PERTALITE TERHADAP MOBIL HEMAT ENERGI “HAIZUM “ - Fahrizal amin, Achmad Nauvalil (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRAKTransportation in the Globalization era focuses on fuel efficiency that is efficient or environmentally friendly, therefore a KMHE event is held which aims to encourage the creation of a transportation that has good fuel efficiency. This study aims to determine effect use of pertamax and Pertalite fuels on energy-efficient cars